Principal's Managerial Strategies to Enhance Teacher Motivation in Junior High Schools - Aida Warni; Nasir Usman; Ismail Ismail; Rizka Zahara; Fitri Setiawati (Journal of General Education and Humanities, 2025)
Teacher motivation is a crucial determinant of learning quality; therefore, the principal's role as an educational manager is highly significant. This study provides new insight into how principals integrate democratic and transformational leadership practices to sustain teacher motivation in regional schools. Specifically, it examines the principals' efforts to optimize school management to enhance teacher motivation at Junior High Schools (SMPs) in Tapaktuan District, South Aceh Regency. Employing a descriptive qualitative approach, data were collected through in-depth interviews with principals, vice principals, and teachers, complemented by observation and document analysis. The data were analyzed using an interactive analysis model, with source triangulation ensuring validity. Findings reveal that the optimization of principal management is achieved through three key dimensions: (1) the implementation of democratic and transformational leadership styles, (2) the development of teacher professionalism through training, mentoring, and collaborative reflection, and (3) the creation of a positive, collegial, and motivating school culture. The study's novelty lies in demonstrating how participatory, innovative, and human-centered management approaches can effectively enhance teacher motivation in regional schools, where challenges often differ from those in urban settings. These findings enrich the educational management literature and offer practical recommendations for school leaders and policymakers on designing sustainable management strategies to strengthen teacher motivation and promote continuous improvement in educational quality.